Effects of Maternal Anthropometry on Infant Anthropometry: A Cross-sectional Study at Public Hospital X in Ternate, Indonesia - Nurwati, Yuni; Hardinsyah, Hardinsyah; Marliyati, Sri Anna; Santoso, Budi Iman; Anggraini, Dewi (UI Scholars Hub, 2024)
Infant anthropometry is an indicator of neonatal survival. This study aimed to determine the effects of maternal anthropometry on estimating infant anthropometry. This cross-sectional study on 173 pregnant women at Public Hospital X in Ternate, Indonesia, was conducted from August 2018 to March 2023. The eligible criteria were pregnant women aged ≥18 years, single pregnancy, and antenatal care (ANC) visits to the same hospital. The variables used included maternal anthropometric measurements (body weight, body height, third-trimester weight (TTW)), gestational weight gain (GWG), education, age, ANC visits, and gestational age at delivery (GAD). A logistic regression model was employed to estimate significant variables related to infant anthropometric measurements (birth weight, birth length, and head circumference). The results showed that TTW, GWG, ANC, and GAD had significantly affected birth weight. Bodyweight, height, and TTW also significantly affected birth length. In addition, only GAD significantly affected the head circumference. In multivariate analysis, TTW and GWG significantly affected birth weight. Furthermore, only body height and GAD affected the birth length. Maternal anthropometrics become important indicators for estimating birth weight and birth length.